When Is Buff Enough? The Effect of Body Attitudes and Narcissistic Traits on Muscle Dysmorphia. Issue 2 (June 2016) - Collis, Nathan; Lewis, Vivienne; Crisp, Dimity
The present study investigated the relationship between narcissistic personality traits, body attitudes, and muscle dysmorphia. Participants were 117 men, aged 18 to 58 years, identifying as men who currently weight train ( n = 78), former weight trainers ( n = 28), or who had never weight trained ( n = 11). Results indicated that male body attitudes were significantly associated with indications of muscle dysmorphia. Moreover, men who currently weight trained reported more positive body attitudes than former weight trainers. Specifically former weight trainers reported significantly more negative body attitudes compared with men who currently weight train if training frequency was reported as once per week or less. No significant association was found between narcissism and muscle dysmorphia. Furthermore, there were no significant differences between current and former weight trainers in levels of narcissism or muscle dysmorphia. These results highlight avenues for further investigation and the importance of understanding the complexity of body image issues in men in clinical practice.